Development of Host- and Symbiont-Specific Monoclonal Antibodies and Confirmation of the Origin of the Symbiosome Membrane in a Cnidarian-Dinoflagellate Symbiosis - Wakefield, Timothy S.; Kempf, Stephen C. (The Biological bulletin (Lancaster), 2001)
The "symbiosome membrane" as defined by Roth et al. (1988) is a single, host-derived membrane that surrounds an endosymbiotic organism, separating it from the cytoplasm of the host cell. However, in the case of cnidarian-dinoflagellate endosymbioses, clear identification of the symbiosome membrane is complicated by the fact that each algal symbiont is surrounded by multiple layers of apparent membrane. The origin and molecular nature of these membranes has been the subject of considerable debate in the literature. Here we report the development of host-specific (G12) and symbiont-specific (PC3) monoclonal antibodies that allow separation of the host and symbiont components of these multiple membranes. Using immunocytochemistry at both the light and the electron microscopic level, we present data supporting the conclusion that the definitive symbiosome membrane is a single, host-derived membrane, whereas the remainder of the underlying apparent membranes surrounding the algal cell are symbiont-derived. The potential for macromolecules associated with these membranes to act as cellular signals critical to recruiting symbionts and maintaining established symbioses is discussed.